Factors Influencing Pregnant Women’s Knowledge Regarding the Utilization of the Maternal and Child Health (MCH) Handbook at PMB Bd. M Bojong Gede in 2025 - Oktya, Tita; Simanjuntak, Roniarta; Radhia, Mekar Zenni; Yolanda, Silvia; Pratiwi, Vita (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: High-quality maternal and child health services are essential for reducing maternal and child mortality. The Maternal and Child Health (MCH/KIA) handbook can be effective when mothers and families actively learn and apply its guidance in daily life. Objective: To identify factors influencing pregnant women’s knowledge regarding the utilization of the MCH handbook at PMB Midwife M, Bojong Gede, during July–August 2025. Method: This survey used a cross-sectional design with total sampling. A total of 55 pregnant women participated. Variables assessed included maternal age, education, occupation, attitude, and other related factors. Data were analyzed using statistical association tests. Results and Discussion: Significant relationships were found between maternal age and knowledge, education and knowledge, maternal occupation and knowledge, and attitude and knowledge regarding MCH handbook utilization. These findings suggest that socio-demographic characteristics and maternal attitudes shape how well pregnant women understand and use the handbook. Conclusion: Four of six examined variables significantly influenced knowledge. Health providers should target mothers with limited understanding to strengthen counseling and promote MCH handbook use across pregnancy, childbirth, postpartum, newborn care, family planning, and child development